Oxford American large print dictionary
In addition to solid coverage of the core English vocabulary, including new words and senses, with definitions that are concise and easy-to-understand, theOxford American Large Print Dictionary also includes thousands of difficult and literary words that are most often looked up. It also includes short, accessible notes on difficult spellings, confusable words, and tricky areas of usage.